2016
DOI: 10.1158/2326-6066.cir-15-0297
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Activation of Hypothalamic BDNF Modulates T-cell Immunity to Exert an Anticancer Phenotype

Abstract: Macro-environmental factors, including a patient’s physical and social environment, play a role in cancer risk and progression. Our previous studies show that living in an enriched environment (EE) providing complex stimuli confers an anticancer phenotype in mice mediated in part by a specific neuroendocrine axis, with brain-derived neurotrophic factor (BDNF) as the key brain mediator. Here we investigated how an EE modulated T-cell immunity and its role in the EE-induced anticancer effects. Our data demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 44 publications
2
50
0
Order By: Relevance
“…Larotrectinib has shown toxicity profile with fatigue, dizziness and memory loss (92). Besides, BDNF in central nervous system, especially hypothalamus, have an oncolytic role by increasing T-cell toxicity (98,100,101). When targeting Trk receptors for treatment of cancer, these drugs will also decrease activity of BDNF/TrkB in the central nervous system and thus may attenuate BDNF-mediated anti-cancer immune response.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Larotrectinib has shown toxicity profile with fatigue, dizziness and memory loss (92). Besides, BDNF in central nervous system, especially hypothalamus, have an oncolytic role by increasing T-cell toxicity (98,100,101). When targeting Trk receptors for treatment of cancer, these drugs will also decrease activity of BDNF/TrkB in the central nervous system and thus may attenuate BDNF-mediated anti-cancer immune response.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Future research is required to elucidate the role of BDNF in these specific hypothalamic nuclei regarding anxiety. Alternatively, we have reported that hypothalamic BDNF modulates the hypothalamic‐pituitary‐adrenal (HPA) axis partially mediating the EE's regulation of T cell immunity (Xiao et al, ). It will be interesting to investigate whether hypothalamic BDNF's modulation of the HPA axis contributes to the anti‐depression effect in the aged animals whose stress response system becomes less agile and dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic tone remodels the adipose tissue, inducing browning of white fat and suppression of leptin, leading to an anti‐obesity and anticancer phenotype (Cao & During, ; Cao et al, ). Furthermore, hypothalamic BDNF modulates secondary lymphoid tissues (spleen and lymph nodes) and enhances CD8 T cell immunity, contributing to the anticancer effects of EE (Xiao et al, ). A reduction in BDNF signaling has been documented during normal aging and decreased BDNF levels are associated with vulnerable neuronal populations in several neurodegenerative disorders including Alzheimer's, Parkinson's and Huntington's diseases, demonstrating the need for further therapeutic research on components of the BDNF signaling pathway (Tapia‐Arancibia, Aliaga, Silhol, & Arancibia, ).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies indicated that environmental and genetic activation of hypothalamic BDNF augments T-cell cytotoxicity to confer an anti-cancer phenotype in melanoma (48) and in glioma (15). This suggests that while autocrine BDNF signaling will most likely promote cancer progression and aggressiveness, BDNF up-regulation restricted to the central nervous system more readily produces a shift toward oncolysis rather than oncogenesis, even if the tumor is localized to the central nervous system (15).…”
Section: Immunoaugmentation: Awakening the Sleeping Giantmentioning
confidence: 99%